Eflapegrastim, a Long‐Acting Granulocyte‐Colony Stimulating Factor for the Management of Chemotherapy‐Induced Neutropenia: Results of a Phase III Trial. (16th June 2020) - Schwartzberg, Lee S.; Bhat, Gajanan; Peguero, Julio; Agajanian, Richy; Bharadwaj, Jayaram S.; Restrepo, Alvaro; Hlalah, Osama; Mehmi, Inderjit; Chawla, Shanta; Hasal, Steven J.; Yang, Zane; Cobb, Patrick Wayne
Abstract: Background: Eflapegrastim, a novel, long‐acting recombinant human granulocyte‐colony stimulating factor (rhG‐CSF), consists of a rhG‐CSF analog conjugated to a human IgG4 Fc fragment via a short polyethylene glycol linker. Preclinical and phase I and II pharmacodynamic and pharmacokinetic data showed increased potency for neutrophil counts for eflapegrastim versus pegfilgrastim. This open‐label phase III trial compared the efficacy and safety of eflapegrastim with pegfilgrastim for reducing the risk of chemotherapy‐induced neutropenia. Materials and Methods: Patients with early‐stage breast cancer were randomized 1:1 to fixed‐dose eflapegrastim 13.2 mg (3.6 mg G‐CSF) or standard pegfilgrastim (6 mg G‐CSF) following standard docetaxel plus cyclophosphamide chemotherapy for 4 cycles. The primary objective was to demonstrate the noninferiority of eflapegrastim compared with pegfilgrastim in mean duration of severe neutropenia (DSN; grade 4) in cycle 1. Results: Eligible patients were randomized 1:1 to study arms (eflapegrastim, n = 196; pegfilgrastim, n = 210). The incidence of cycle 1 severe neutropenia was 16% ( n = 31) for eflapegrastim versus 24% ( n = 51) for pegfilgrastim, reducing the relative risk by 35% ( p = .034). The difference in mean cycle 1 DSN (−0.148 day) met the primary endpoint of noninferiority ( p < .0001) and also showed statistical superiority for eflapegrastim ( p = .013). Noninferiority was maintained for the duration of treatment (all cycles, p < .0001), and secondary efficacy endpoints and safety results were also comparable for study arms. Conclusion: These results demonstrate noninferiority and comparable safety for eflapegrastim at a lower G‐CSF dose versus pegfilgrastim. The potential for increased potency of eflapegrastim to deliver improved clinical benefit warrants further clinical study in patients at higher risk for CIN. Implications for Practice: Chemotherapy‐induced neutropenia (CIN) remains a significant clinical dilemma for oncology patients who are striving to complete their prescribed chemotherapy regimen. In a randomized, phase III trial comparing eflapegrastim to pegfilgrastim in the prevention of CIN, the efficacy of eflapegrastim was noninferior to pegfilgrastim and had comparable safety. Nevertheless, the risk of CIN remains a great concern for patients undergoing chemotherapy, as the condition frequently results in chemotherapy delays, dose reductions, and treatment discontinuations. Abstract : Myelosuppression, particularly neutropenia, has presented a major challenge in cancer treatment since the introduction of cytotoxic chemotherapy. This article reports the results of a phase III trial that compared the efficacy and safety of eflapegrastim with pegfilgrastim for reducing the risk of chemotherapy‐induced neutropenia.